The effect of processing conditions for polylactic acid based fibre composites via twin-screw extrusion. (April 2014) - Gunning, Michael A; Geever, Luke M; Killion, John A; Lyons, John G; Higginbotham, Clement L
Hemp, jute and lyocell fibres were incorporated into polylactic acid via twin-screw extrusion using three screw configurations, with varying lengths of mixing sections, in order to reduce the levels of shear and fibre attrition. When mixing zones were reduced, the measured fibre lengths increased and as a result the tensile properties of polylactic acid composites were improved. Similarly impact properties were observed to improve as fibre length increased. However, by increasing the fibre length in polylactic acid composites, fibre surface area within the composite was reduced and subsequently the rate of biodegradation decreased. Composites prepared using different extrusion temperature profiles were shown to have vastly different mechanical properties and in all cases composites produced using low temperature profiles exhibited superior properties to those produced at higher temperatures, indicating thermal degradation at the more elevated temperatures. For example, 50 wt% jute composites exhibited increases of 20.9% and 199% in tensile strength and flexural modulus, the greatest improvement of all composite types at that loading.